DEFINITIONAL PROBLEMS OF ACCOUNTING POLICY (Research Bulletins of the Faculty of Economic Sciences, 2021)
The article signaled a problem with the alternatively use of terms such as account-ing policy, accounting principles and earnings management. Furthermore this paper pointed out the problem of disagreement regarding methodof defining creative account-ing.
Keywords: accounting, accounting policy, accounting principles and earnings management